The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4315/0362-028x.jfp-14-487
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation of Foodborne Enteric Viruses and Their Viral Surrogates in Foods

Abstract: Foodborne viruses, in particular human norovirus and hepatitis A virus, are the most common causes of food-associated infections and foodborne illness outbreaks around the world. Since it is currently not possible to cultivate human noroviruses and the wild-type strain of hepatitis A virus in vitro, the use of a variety of viral surrogates is essential to determine appropriate thermal processing conditions to reduce the risk associated with their contamination of food. Therefore, the objectives of this review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 110 publications
1
50
0
Order By: Relevance
“…Traditionally, for the first‐order kinetic model, the change in number of survivors over time has been described using the following equation of a straight line (Bozkurt, D'Souza, & Davidson, ; ; , Bozkurt, Ye et al., ): NtN0t=ekt,where – k is slope (and D = –1/slope), N ( t ) is the number of survivors after an exposure/treatment time ( t ) in PFU/mL, and N 0 is initial target population (PFU/mL). The D ‐values for different temperatures were plotted on semilog coordinates, and the temperature change for a one log‐cycle change in D ‐values was calculated as the z ‐value as previously reported (Bozkurt, Ye et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, for the first‐order kinetic model, the change in number of survivors over time has been described using the following equation of a straight line (Bozkurt, D'Souza, & Davidson, ; ; , Bozkurt, Ye et al., ): NtN0t=ekt,where – k is slope (and D = –1/slope), N ( t ) is the number of survivors after an exposure/treatment time ( t ) in PFU/mL, and N 0 is initial target population (PFU/mL). The D ‐values for different temperatures were plotted on semilog coordinates, and the temperature change for a one log‐cycle change in D ‐values was calculated as the z ‐value as previously reported (Bozkurt, Ye et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Historically and traditionally, thermal inactivation has been most widely used to inactivate pathogens in food and for food preservation. Heat causes protein denaturation of viral capsids resulting in noninfectious viral subunits and single individual proteins (Bozkurt, D'Souza, & Davidson, ; Song et al., ). Above 60 °C, after the inactivation/destruction of host‐cell recognition and binding receptors, an alteration of the tertiary protein structure is reported to occur that can facilitate the access of thermal energy to the nucleic acids (Ausar, Foubert, Hudson, Vedvick, & Middaugh, ; Bertrand et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS2 phage was used as a model because of its similar size (&22-29 nm), the presence of a positive-sense RNA genome, and an overall structure of the capsid close to enteric pathogenic viruses (Bae and Schwab 2008;Boudaud et al 2012;Bozkurt et al 2015;Deboosere et al 2012;Shirasaki et al 2009;Sidhu and Toze 2009;Valegård et al 1990). This phage is non-pathogenic for humans and easy to culture in laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been shown that virus inactivation by thermal processing does not follow a linear inactivation model (firstorder kinetics), which assumes a linear logarithmic reduction of the quantity of the treated virus with time (45). A virus thermal inactivation curve usually shows shouldering and tailing at the beginning and end of the survival curve, respectively, limiting the ability to use decimal reduction times (D values) to establish the inactivation parameters.…”
mentioning
confidence: 99%